Elephant herbivory in Majete Wildlife Reserve, Malawi. (8th January 2013) - Staub, Caroline G.; Binford, Michael W.; Stevens, Forrest R.
Abstract: Elephants have a major influence on vegetation structure, composition and ecosystem processes, and are primary agents of habitat change in Africa. At moderate‐to‐high population densities, elephants can damage vegetation, especially when enclosed in protected areas. This study examines the effects of elephant browsing on woody trees in Majete Wildlife Reserve (WR), south‐western Malawi. Regression analysis is used to assess the associations of six factors known to drive elephant browsing in other areas and determine which ones have the most influence on browsing at Majete WR. Twenty‐four per cent of tagged trees had been subject to elephant browsing. The model with vegetation type, stem diameter and distance from permanent water correctly predicted browsing for 80% of the observations. Elephants mostly favoured riparian woodlands, followed by Acacia ‐dominated woodland and Brachystegia ‐dominated woodland. Browsing occurrence was negatively related to distance from permanent water and diameter at breast height(DBH). A larger number of trees, sampled at random and covering a larger portion of the reserve would provide more reliable estimates of browsing and related factors. Knowledge of time‐ and site‐specific factors affecting elephant browsing can be used to forecast future habitat transformations and manipulate the range of the elephants within the reserve.